Urbanisation and its effect on risk factors associated with childhood diarrhoea in Mbour, Senegal: A visualisation - Sokhna Thiam; Samuel Fuhrimann; Aminata Niang-Diène; Ibrahima Sy; Ousmane Faye; Jürg Utzinger; Guéladio Cissé (Geospatial Health, 2017)
Rapid urbanisation, particularly in secondary cities in Africa, brings along specific challenges for global health, including the prevention and control of infectious diseases such as diarrhoea. Our purpose was to visualise urbanisation trends and its effect on risk factors associated with childhood diarrhoea, e.g. water supply, sanitation, wastewater and solid waste management in Mbour, a secondary city in south-western Senegal. Our visualisation is facilitated by epidemiological and geographical surveys carried out in 2016. A deeper spatial and visual understanding of the urbanisation trends and the disparities of diarrhoea-associated risk factors might lead to the implementation of suitable health interventions and preventive measures. Our visualisation is aimed to serve as a basis for discussion and as a decision support tool for policymakers, municipal officials and local communities to prioritise interventions related to water, sanitation and waste management with a view to reduce the environmental and health risks in the rapidly growing city of Mbour, which is set as an example for other similar secondary cities across low- and middle-income countries in Africa.